Silver-coated copper-based composite microspheres regulated by nickel component interface, preparation method and application
Patent Information
- Application Number
- CN202611230065.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]本发明的目的在于提供一种镍组分界面调控的银包覆铜基复合微球、制备方法及应用,解决了现有技术中银包铜复合微球在高温固化过程中因Cu/Ag界面贴合不足导致导电性能严重衰减,以及依赖连续镍中间壳层所带来的制备复杂和接触电阻增大的问题
[0016]本发明的一种镍组分界面调控的银包覆铜基复合微球、制备方法及应用,先对铜基微球进行敏化活化预处理,再将预处理后的铜基微球置于含镍盐、醋酸钠、乙二胺四乙酸二钠和对苯二酚的酸性反应液中,以次亚磷酸钠为还原剂进行短时化学还原沉积,使镍和磷组分分布于铜基微球的表面及近表面区域,得到Ni-Cu复合微球前驱体;随后将该前驱体分散于含葡萄糖和络合组分的水与乙醇混合体系中,以银氨络合前体为银源,在碱性条件下进行化学还原沉积,使银富集于颗粒外部,最终获得镍组分不形成清晰连续独立中间壳层的银包覆Ni-Cu复合微球。本发明通过镍和磷组分在铜基微球表面及近表面的非连续复合引入,对后续银沉积界面进行调控,有效减少了Ag外部区域与Cu基体之间的界面间隙;将该复合微球作为导电填料应用于高温固化导电浆料时,在280℃空气中固化120分钟后,导电膜电阻率可低至144μΩ·cm,与直接银包铜复合微球相比,在相同条件下具有显著更优的长时间高温导电稳定性,同时避免了连续镍中间壳层的构筑,简化了制备工艺并降低了颗粒间接触电阻,从而有效解决了现有技术中银包铜复合微球在高温固化过程中因Cu/Ag界面贴合不足导致导电性能严重衰减的问题。
Smart Images

Figure CN122955935A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of copper-based conductive filler technology, and in particular to a silver-coated copper-based composite microsphere with nickel component interface regulation, its preparation method, and its application. Background Technology
[0002] Silver, with its excellent conductivity and high chemical stability, has become one of the most widely used conductive phases in electronic pastes. However, excessive silver usage significantly increases material costs, and under specific humid and hot environments and bias conditions, silver is prone to electrochemical migration, leading to reliability issues such as short circuits, limiting its application in high-density interconnects and high-reliability scenarios. Copper, with its similar bulk resistivity to silver and low cost, is an ideal candidate to replace silver as a conductive phase. However, during storage, paste preparation, and subsequent heat treatment, micron- or submicron-sized copper powder readily forms low-conductivity oxides such as Cu₂O and CuO on its surface. These oxides significantly increase the contact resistance between particles, weaken the integrity of the conductive network, and thus reduce conductivity. To balance conductivity and cost while improving oxidation resistance, the technique of depositing silver on the surface of copper particles to form Cu@Ag composite particles has attracted widespread attention.
[0003] In existing Cu@Ag composite particle preparation technologies, the nucleation and growth process of silver, as well as its subsequent thermal evolution, are closely related to the surface state of the copper substrate, the complexation equilibrium of the plating solution, the reduction reaction rate, and the Cu / Ag interface structure. If the silver deposition process is not properly controlled, or if rearrangement, local shrinkage, or pore enlargement occurs in the outer silver layer during subsequent heat treatment, significant interfacial gaps can easily form between the Ag outer region and the Cu substrate. The formation of these interfacial gaps exposes the copper substrate back to air, leading to accelerated oxidation during high-temperature curing and consequently a significant decrease in conductivity, severely limiting the practical application of Cu@Ag composite particles in high-temperature cured conductive pastes. To suppress copper oxidation and the interdiffusion between silver and copper, existing technologies have disclosed Cu@Ni@Ag three-layer conductive powder structures with a copper core, a continuous nickel interlayer, and a silver outer layer, where the continuous nickel interlayer is intended to act as a barrier. However, constructing an additional continuous and dense nickel interlayer not only increases the difficulty of preparation steps and process control but may also introduce higher contact resistance between particles, negatively impacting conductivity. At the same time, even with this structure, the inherent problem of insufficient Cu / Ag interface adhesion in direct chemical silver plating has not been fundamentally solved.
[0004] Therefore, how to improve the interfacial bonding between the silver outer layer and the copper substrate while avoiding the formation of a continuous nickel intermediate shell, and how to enhance the conductivity stability of the composite microspheres during long-term high-temperature curing, has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] The purpose of this invention is to provide a silver-coated copper-based composite microsphere with nickel component interface regulation, its preparation method, and its application. This invention solves the problems in the prior art where the conductivity of silver-coated copper composite microspheres is severely degraded due to insufficient Cu / Ag interface adhesion during high-temperature curing, as well as the complexity of preparation and increased contact resistance caused by relying on a continuous nickel intermediate shell.
[0006] To achieve the above objectives, this invention provides a method for preparing silver-coated copper-based composite microspheres with nickel component interface regulation, comprising the following steps: Copper-based microspheres were degreased, acid-washed, and water-washed, and then sensitized using a mixture of SnCl2 and HCl, and activated using a mixture of PdCl2 and HCl to obtain activated copper-based microspheres. The activated copper-based microspheres were dispersed in an acidic reaction solution containing nickel salt, sodium acetate, disodium ethylenediaminetetraacetate, and hydroquinone. Sodium hypophosphite was added at a temperature of 30-100 °C for chemical reduction deposition, and the reaction time was 5-60 min. This allowed the Ni and P components to be distributed on the surface and near-surface region of the copper-based microspheres, resulting in a Ni-Cu composite microsphere precursor. The Ni-Cu composite microsphere precursor was dispersed in a water and ethanol mixture containing glucose and a complexing component. A silver complexing precursor containing AgNO3 and triethylenetetramine was then added. + Chemical reduction deposition was carried out under conditions of concentration of 5.81~11.49 mmol / L, pH of 8.0~10.0, and reaction temperature of 10~35 ℃ for 15~120 min to obtain the reaction product; The reaction products were separated, washed, and dried to obtain silver-coated Ni-Cu composite microspheres in which silver was enriched on the outside of the particles and the Ni component did not form a clear, continuous, and independent intermediate shell.
[0007] The copper-based microspheres are spherical or near-spherical copper powders with an average particle size of 1-3 μm.
[0008] Specifically, using 0.3 g of the copper-based microspheres as a reference, "dispersing the activated copper-based microspheres in an acidic reaction solution containing nickel salt, sodium acetate, disodium ethylenediaminetetraacetate, and hydroquinone" includes: The following solutions were used: 20 mL of 0.116 mol / L NiSO4·6H2O solution, 10 mL of 0.122 mol / L sodium acetate solution, and 1.02 × 10⁻⁶ ppm sodium acetate solution. -4 mol ethylenediaminetetraacetic acid disodium dihydrate and 2.99 × 10 -4 Prepare the acidic reaction solution using mol of hydroquinone; Add 10 mL of 0.943 mol / L NaH2PO2·H2O solution and react for 15 minutes at 70℃ and pH 4.5~5.0.
[0009] Specifically, "dispersing the activated copper-based microspheres in an acidic reaction solution containing nickel salt, sodium acetate, disodium ethylenediaminetetraacetate, and hydroquinone" includes: The mass ratio of the copper-based microspheres to the nickel source is 2:1.
[0010] The process preceding "dispersing the Ni-Cu composite microsphere precursor in a mixed system of water and ethanol containing glucose and complexing components" specifically includes: The Ni-Cu composite microsphere precursor was surface-treated using a mixture of 7 mol / L ammonia and 0.024 mol / L ammonium sulfate.
[0011] Specifically, "dispersing the Ni-Cu composite microsphere precursor in a mixed system of water and ethanol containing glucose and complexing components" includes: The volume ratio of the water and ethanol mixture is 4:1; The mixed system also includes sodium tartrate, polyethylene glycol, and alkylphenol polyoxyethylene ether NP-40; Based on an AgNO3 concentration of 2.35 mmol, the dosage of glucose is 16.7 mmol, sodium tartrate is 5.2 mmol, and disodium EDTA is 3.2 mmol.
[0012] Specifically, "addition of a silver complex precursor containing AgNO3 and triethylenetetramine" includes: The silver complex precursor was prepared by adding triethylenetetramine dropwise to an aqueous solution containing AgNO3 until the milky white precipitate disappeared and a clear solution was obtained. The Ag + The concentration was 8.67 mmol / L, the pH was 9.0, and the reaction time was 60 minutes.
[0013] Specifically, "separating, washing, and drying the reaction products" includes: The reaction product was washed with deionized water and ethanol and then dried under vacuum at 50°C for 3 hours.
[0014] The silver-coated copper-based composite microspheres with nickel component interface regulation are described. The silver-coated Ni-Cu composite microspheres are mainly composed of copper-based microspheres. The Ag signal is located on the outside of the particles, and the Ni signal is spatially correlated with the Cu-based region. The nickel component does not form a clear and continuous independent intermediate shell.
[0015] The application of the nickel-component interface-controlled silver-coated copper-based composite microspheres as conductive fillers in high-temperature curing conductive slurries.
[0016] This invention discloses a silver-coated copper-based composite microsphere with nickel component interface regulation, its preparation method, and its application. First, the copper-based microspheres undergo sensitization and activation pretreatment. Then, the pretreated copper-based microspheres are placed in an acidic reaction solution containing nickel salt, sodium acetate, disodium EDTA, and hydroquinone. Short-term chemical reduction deposition is performed using sodium hypophosphite as a reducing agent, causing nickel and phosphorus components to distribute on the surface and near-surface region of the copper-based microspheres, yielding a Ni-Cu composite microsphere precursor. Subsequently, this precursor is dispersed in a water-ethanol mixture containing glucose and a complexing component. Using a silver ammonia complex precursor as the silver source, chemical reduction deposition is performed under alkaline conditions, enriching the silver on the outside of the particles. Finally, silver-coated Ni-Cu composite microspheres are obtained where the nickel component does not form a clear, continuous, and independent intermediate shell. This invention introduces nickel and phosphorus components discontinuously onto the surface and near the surface of copper-based microspheres to regulate the subsequent silver deposition interface, effectively reducing the interfacial gap between the Ag outer region and the Cu matrix. When this composite microsphere is used as a conductive filler in a high-temperature curing conductive slurry, the resistivity of the conductive film can be as low as 144 μΩ·cm after curing in air at 280°C for 120 minutes. Compared with direct silver-coated copper composite microspheres, it exhibits significantly better long-term high-temperature conductivity stability under the same conditions. At the same time, it avoids the construction of a continuous nickel intermediate shell, simplifies the preparation process, and reduces the interparticle contact resistance, thus effectively solving the problem of severe conductivity degradation caused by insufficient Cu / Ag interface adhesion during high-temperature curing of silver-coated copper composite microspheres in the prior art. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.
[0018] Figure 1 This is a flowchart of the preparation method of the nickel component interface-controlled silver-coated copper-based composite microspheres of the present invention.
[0019] Figure 2 This is a diagram showing the cross-sectional morphology, Cu / Ni elemental distribution, and local elemental content of the reduced-treated Ni-Cu composite microspheres of the present invention.
[0020] Figure 3 These are the surface morphology, EDS elemental distribution, overall elemental content, and line scan results of the Ni-Cu@Ag composite microspheres under the optimized conditions of this invention.
[0021] Figure 4 These are FIB cross-sectional morphology, elemental distribution of the interface region, and EDS line scan results of the direct Cu@Ag composite microspheres of the present invention.
[0022] Figure 5 These are FIB cross-sectional morphology, elemental distribution of the interface region, and EDS line scan results of the Ni-Cu@Ag composite microspheres of the present invention.
[0023] Figure 6 These are the morphology and XRD results of the direct Cu@Ag composite microspheres of the present invention after being kept in air at 250°C for 10, 20 and 30 minutes.
[0024] Figure 7 These are the morphology and XRD results of the Ni-Cu@Ag composite microspheres of the present invention after being kept in air at 250°C for 10, 20 and 30 minutes.
[0025] Figure 8 This is a comparison of the resistivity of the direct Cu@Ag and Ni-Cu@Ag conductive films of the present invention under different curing times in air at 280°C.
[0026] Figure 9 This is a flowchart illustrating the steps of the preparation method of the nickel-component interface-controlled silver-coated copper-based composite microspheres of the present invention. Detailed Implementation
[0027] The embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, but should not be construed as limiting the present invention.
[0028] Unless otherwise stated, "room temperature" in this embodiment refers to 10~35 °C; "slow addition" means adding under conditions that maintain particle dispersion and avoid excessive local silver deposition; "Ag-enriched external region" means that the Ag signal in EDS surface distribution or line scan is mainly located at the outer edge of the particles, and does not mean that the Ag layer has the same thickness at all locations. "Ni-Cu composite microspheres" refers to composite particles with Cu-based microspheres as the main body and the Ni / P component associated with the Cu-based surface and near-surface region, and does not necessarily mean that a continuous Ni shell exists. "Ni-Cu@Ag" indicates that an Ag-enriched region is further formed outside the Ni-Cu composite microspheres.
[0029] Please see Figures 1 to 9 Example 1: Preparation of Ni-Cu composite microsphere precursor: Commercially available high-purity spherical or near-spherical Cu powder with an average particle size of approximately 1–3 μm was selected. The powder was sequentially washed with ethanol, dilute acid, and deionized water to remove organic contaminants and surface oxides. It was then sensitized using a SnCl2 / HCl system and activated using a PdCl2 / HCl system. After water washing, it was immediately used for Ni component deposition. The accurate concentrations and treatment times of the sensitization and activation solutions were based on the original experimental records of the same batch, and these records should be solidified before formal application.
[0030] Using 0.3 g Cu powder as a reference, 20 mL of 0.116 mol / L NiSO4·6H2O solution and 10 mL of 0.122 mol / L sodium acetate solution were mixed, and 1.02 × 10⁻⁶ ppm was added. -4 mol EDTA-2Na·2H2O and 2.99×10 -4 Adjust the pH to 4.5–5.0 using hydroquinone. Add activated Cu powder and disperse by stirring at 70 °C. Slowly add 10 mL of 0.943 mol / L NaH₂PO₂·H₂O solution and react for 15 min. Separate the solid, wash successively with deionized water and ethanol, and dry under vacuum at 50 °C for 3 h to obtain the Ni-Cu composite microsphere precursor.
[0031] The overall EDS analysis of representative samples showed Cu, Ni, and P mass fractions of 87.04%, 10.59%, and 2.37%, respectively. After treatment in an Ar / H2 atmosphere at 300 °C for 30–180 min, the local cross-sectional EDS analysis of representative samples showed Cu and Ni mass fractions of 85.48% and 14.52%, respectively. The Cu and Ni signals showed spatial overlap in the particle cross-section, as shown in the image. Figure 2 As shown. This reduced sample is used to aid in elucidating the Ni-Cu composite structure and is not equivalent to a quantitative definition of all untreated precursors.
[0032] Example 2, Ni-Cu precursor process window: The amount of NaH₂PO₂·H₂O added, the Cu / Ni feed ratio, and the reaction pH were varied. The NaH₂PO₂·H₂O added amounts were 0, 1.887, 3.774, 5.661, 7.548, and 9.435 mmol; the Cu / Ni feed ratios were 3:1, 3:1.5, 3:2, 3:4, 3:5, 3:6, and 3:7; and the pH values were 3.5, 4.0, 4.5, 5.0, 5.5, and 6.0. Considering the compatibility of Ni introduction, particle dispersion, and subsequent Ag deposition, 9.435 mmol of NaH₂PO₂·H₂O, a Cu / Ni ratio of 3:1.5, and a pH of 4.5–5.0 were considered optimal conditions. Further increases in Ni feed resulted in a Ni content exceeding approximately 20%, accompanied by significant bridging deposition and agglomeration, which is detrimental to pulping and printing.
[0033] Table 1 Results of process window investigation for Ni-Cu composite microsphere precursor preparation
[0034] Example 3: Preparation of Ni-Cu@Ag composite microspheres: The Ni-Cu composite microsphere precursor obtained in Example 1 was surface-treated with a mixed solution containing 7 mol / L ammonia and 0.024 mol / L ammonium sulfate, washed with water, and then dispersed in a mixed solvent with a water / ethanol volume ratio of 4:1.
[0035] Based on an AgNO3 concentration of 2.35 mmol, 16.7 mmol of glucose, 5.2 mmol of sodium tartrate, and 3.2 mmol of EDTA-2Na were added; polyethylene glycol and NP-40 were also added to improve dispersion and deposition uniformity. AgNO3 was dissolved in deionized water, and triethylenetetramine was added dropwise with stirring; initially, a milky white precipitate formed, and triethylenetetramine was continued to be added until the precipitate disappeared and a clear silver complex precursor was obtained. The silver complex precursor was slowly added to the Ni-Cu precursor dispersion, and the final AgNO3 concentration was adjusted by adding a water / ethanol mixture. + The concentration was 8.67 mmol / L, and the pH was adjusted to 9.0 with 0.5 mol / L NaOH. The reaction was carried out at 10–35 °C for 60 min. After the reaction was completed, the solid was separated, washed with water and ethanol, and dried under vacuum at 50 °C for 3 h.
[0036] like Figure 3 As shown, the surface of the representative Ni-Cu@Ag sample is composed of nanoscale Ag grains; the overall EDS measurements showed that the mass fractions of Cu, Ni, and Ag were 46.88%, 8.30%, and 44.82%, respectively. In single-particle line scanning, the Ag signal was enhanced at the edges of both sides of the particle, the Cu signal was mainly located inside, and the Ni signal was weak and corresponded to the Cu-based region.
[0037] The mass fractions of Ni, Cu, and Ag measured by EDS at a representative local section of the FIB were 1.39%, 92.40%, and 6.21%, respectively. Figure 5 As shown in the figure. This value represents a local cross-sectional area, which differs from the overall EDS sampling volume, and therefore cannot be directly used to calculate the overall Ni loss or total Ag content.
[0038] HRTEM revealed an Ag(111) interplanar spacing of approximately 2.41 Å in the outer region and a Cu(111) interplanar spacing of approximately 2.16 Å in the interface and inner region. XPS showed Ag as metallic Ag. 0 The main characteristic is that the surface Ni 2p3 / 2 is located at approximately 855.88 eV with a satellite peak at approximately 860.68 eV, indicating that the detectable Ni on the surface is mainly in the form of Ni. 2+ Related species. The above results are used to illustrate the local crystal and surface chemical states of representative samples and are not intended as evidence of the existence of a continuous Ni shell.
[0039] Example 4, Ag deposition process window: Under the same conditions, examine Ag separately.+ Concentrations of 5.81, 8.67, 11.49, 14.27, and 17.02 mmol / L; pH values of 8.0, 8.5, 9.0, 9.5, and 10.0; and reaction times of 15, 30, 60, 90, and 120 min were observed. The experimental results indicate that Ag... + When the concentration is too low, the coating is insufficient; when it is too high, the Cu matrix is easily consumed excessively, free Ag increases, or hollowing occurs. Too low or too high pH is not conducive to particle integrity. Too short a reaction time results in insufficient deposition, while too long a reaction time increases pores and shell coarsening.
[0040] Table 2 Results of Ag chemical reduction deposition process window investigation
[0041] Comparative Example 1: Direct Cu@Ag composite microspheres: Except for the absence of Ni / P component introduction, the same Cu powder surface treatment, Ag complexation reduction system, and Ag were used as in Example 3. + Direct Cu@Ag composite microspheres were prepared under controlled concentration, pH, temperature, time, and separation and drying conditions.
[0042] like Figure 4 As shown, in representative Cu@Ag particles, the Ag signal is located on the outside and the Cu signal is located inside, but there is a clear interface gap between the Ag outer region and the Cu interior. In contrast, Figure 5 No obvious continuous interface separation was observed in the representative Ni-Cu@Ag particles shown.
[0043] Test Example 1: Air heat treatment at 250℃: Direct Cu@Ag and Ni-Cu@Ag samples were placed in air at 250 °C for 10, 20, and 30 min, respectively. Pores gradually appeared in the Ag outer region of the direct Cu@Ag particles with increasing holding time, such as... Figure 6 As shown, the overall morphology of the Ni-Cu@Ag particles remained largely intact, and no continuous cracking or delamination of the same degree was observed. Figure 7 As shown.
[0044] No obvious Cu2O or CuO diffraction peaks were detected in either type of sample under the corresponding XRD detection conditions. This result only indicates the phase state at 250 ℃, a maximum of 30 min, and the corresponding instrument detection limit, and does not mean that the sample will not undergo oxidation at any temperature, time, or detection sensitivity.
[0045] Test Example 2: Conductive paste and curing at 280°C: Conductive films were prepared using direct Cu@Ag and Ni-Cu@Ag as conductive fillers, respectively, under the same slurry matrix, powder solid content, mixing, grinding, and screen printing conditions, and cured in air at 280 °C for 1, 2, 3, 10, 20, 30, 60, and 120 min. The main components of the slurry included 80 parts by weight of conductive filler, 8 parts by weight of bisphenol A epoxy resin, 2 parts by weight of methylnadic anhydride, 5 parts by weight of reactive diluent, and 5 parts by weight of propylene glycol; 1 part by weight of 2-methylimidazolium, butyl acetate, tetraethyl titanate, and polyamide wax as process aids.
[0046] The resistivity of the direct Cu@Ag conductive film at the above curing times was 54.34, 365.2, 628.12, 832.92, 1196.8, 1858.2, 1918.4 and 3935.36 μΩ·cm, respectively; that of the Ni-Cu@Ag conductive film was 1476, 1479, 1440, 324, 312, 282, 216 and 144 μΩ·cm, respectively. The results are as follows... Figure 8 As shown in Table 3.
[0047] Table 3. Comparison of resistivity of direct Cu@Ag and Ni-Cu@Ag conductive films at different curing times.
[0048] In the initial stage of curing, the resistivity of the Ni-Cu@Ag conductive film is relatively high, indicating that the solvent and organic components have not been fully removed and an effective contact network between particles has not yet been formed. After curing for 10 minutes, its resistivity decreases significantly and continues to decline. Direct Cu@Ag, on the other hand, continuously increases with prolonged curing time. After 120 minutes of curing, the resistivity of Ni-Cu@Ag is approximately 1 / 27.3 that of direct Cu@Ag, indicating that the two exhibit significantly different long-term high-temperature conductive evolution behaviors.
[0049] Using Ni-Cu@Ag conductive paste, flexible conductive lines and interdigitated electrodes can be formed through screen printing, and lighting demonstrations can be completed.
[0050] Compared to direct silver-coated copper composite microspheres, this invention introduces nickel and phosphorus components discontinuously onto the surface and near the surface of copper-based microspheres, thereby controlling the subsequent silver deposition interface. This results in no obvious continuous interface separation between the Ag outer region and the Cu matrix of the obtained silver-coated Ni-Cu composite microspheres. After being incubated at 250°C in air for 30 minutes, the overall particle morphology remains largely intact, avoiding cracking and delamination of the silver outer layer. When this composite microsphere is used as a conductive filler in a high-temperature curing conductive slurry, the resistivity of the conductive film can be as low as 144 μΩ·cm after curing at 280°C in air for 120 minutes, approximately 1 / 27.3 of the resistivity of direct silver-coated copper composite microspheres under the same conditions. This significantly improves the conductivity stability during long-term high-temperature curing, while avoiding the construction of a continuous nickel intermediate shell, simplifying the preparation process and reducing interparticle contact resistance. This effectively solves the problem of severe conductivity degradation caused by insufficient Cu / Ag interface adhesion during high-temperature curing of silver-coated copper composite microspheres in the prior art.
[0051] The above-disclosed embodiments are merely one or more preferred embodiments of this application and should not be construed as limiting the scope of this application. Those skilled in the art can understand that all or part of the processes for implementing the above embodiments and equivalent changes made in accordance with the claims of this application still fall within the scope of this application.
Claims
1. A method for preparing silver-coated copper-based composite microspheres with nickel component interface regulation, characterized in that, Includes the following steps: Copper-based microspheres were degreased, acid-washed, and water-washed, and then sensitized using a mixture of SnCl2 and HCl, and activated using a mixture of PdCl2 and HCl to obtain activated copper-based microspheres. The activated copper-based microspheres were dispersed in an acidic reaction solution containing nickel salt, sodium acetate, disodium ethylenediaminetetraacetate, and hydroquinone. Sodium hypophosphite was added at a temperature of 30-100 °C for chemical reduction deposition, and the reaction time was 5-60 min. This allowed the Ni and P components to be distributed on the surface and near-surface region of the copper-based microspheres, resulting in a Ni-Cu composite microsphere precursor. The Ni-Cu composite microsphere precursor was dispersed in a water and ethanol mixture containing glucose and a complexing component. A silver complexing precursor containing AgNO3 and triethylenetetramine was then added. + Chemical reduction deposition was carried out under the conditions of concentration of 5.81~11.49 mmol / L, pH of 8.0~10.0, and reaction temperature of 10~35 ℃ for 15~120 min to obtain the reaction product; The reaction products were separated, washed, and dried to obtain silver-coated Ni-Cu composite microspheres in which silver was enriched on the outside of the particles and the Ni component did not form a clear, continuous, and independent intermediate shell.
2. The preparation method of silver-coated copper-based composite microspheres with nickel component interface regulation as described in claim 1, characterized in that, The copper-based microspheres are spherical or near-spherical copper powders with an average particle size of 1~3 μm.
3. The preparation method of silver-coated copper-based composite microspheres with nickel component interface regulation as described in claim 1, characterized in that, Using 0.3 g of the copper-based microspheres as a reference, "dispersing the activated copper-based microspheres in an acidic reaction solution containing nickel salt, sodium acetate, disodium ethylenediaminetetraacetate, and hydroquinone" specifically includes: The following solutions were used: 20 mL of 0.116 mol / L NiSO4·6H2O solution, 10 mL of 0.122 mol / L sodium acetate solution, and 1.02 × 10⁻⁶ ppm sodium acetate solution. -4 mol ethylenediaminetetraacetic acid disodium dihydrate and 2.99 × 10 -4 Prepare the acidic reaction solution using mol of hydroquinone; Add 10 mL of 0.943 mol / L NaH2PO2·H2O solution and react for 15 minutes at 70℃ and pH 4.5~5.
0.
4. The preparation method of silver-coated copper-based composite microspheres with nickel component interface regulation as described in claim 1, characterized in that, "Dispersing the activated copper-based microspheres in an acidic reaction solution containing nickel salt, sodium acetate, disodium ethylenediaminetetraacetate, and hydroquinone" specifically includes: The mass ratio of the copper-based microspheres to the nickel source is 2:
1.
5. The preparation method of silver-coated copper-based composite microspheres with nickel component interface regulation as described in claim 1, characterized in that, Before "dispersing the Ni-Cu composite microsphere precursor in a mixed system of water and ethanol containing glucose and complexing components", the specific steps include: The Ni-Cu composite microsphere precursor was surface-treated using a mixture of 7 mol / L ammonia and 0.024 mol / L ammonium sulfate.
6. The preparation method of silver-coated copper-based composite microspheres with nickel component interface regulation as described in claim 1, characterized in that, "Dispersing the Ni-Cu composite microsphere precursor in a mixed system of water and ethanol containing glucose and complexing components" specifically includes: The volume ratio of the water and ethanol mixture is 4:1; The mixed system also includes sodium tartrate, polyethylene glycol, and alkylphenol polyoxyethylene ether NP-40; Based on an AgNO3 concentration of 2.35 mmol, the dosage of glucose is 16.7 mmol, sodium tartrate is 5.2 mmol, and disodium EDTA is 3.2 mmol.
7. The method for preparing silver-coated copper-based composite microspheres with nickel component interface regulation as described in claim 1, characterized in that, The phrase "addition of a silver complex precursor containing AgNO3 and triethylenetetramine" specifically includes: The silver complex precursor was prepared by adding triethylenetetramine dropwise to an aqueous solution containing AgNO3 until the milky white precipitate disappeared and a clear solution was obtained. The Ag + The concentration was 8.67 mmol / L, the pH was 9.0, and the reaction time was 60 minutes.
8. The method for preparing silver-coated copper-based composite microspheres with nickel component interface regulation as described in claim 1, characterized in that, The phrase "separating, washing, and drying the reaction products" specifically includes: The reaction product was washed with deionized water and ethanol and then dried under vacuum at 50°C for 3 hours.
9. A nickel-component interface-controlled silver-coated copper-based composite microsphere, prepared by the method for preparing nickel-component interface-controlled silver-coated copper-based composite microspheres according to claim 1, characterized in that, The silver-coated Ni-Cu composite microspheres are mainly composed of copper-based microspheres. The Ag signal is located on the outside of the particles, and the Ni signal is spatially correlated with the Cu-based region. The nickel component does not form a clear and continuous independent intermediate shell.
10. The application of the nickel-component interface-controlled silver-coated copper-based composite microspheres according to claim 9 as a conductive filler in a high-temperature curing conductive slurry.
